Study on The Potential Contamination of Heavy Metals: Analysis of Cr and Pb Contents From Power Plants in Indonesia Using the Batch Leaching Method - Hanum, Farrah Fadhillah; Salamah, Siti; Rifai Sanuhung, Ahmad; Setya Wardhana, Budi (Universitas Nusa Bangsa, 2024)
Coal ash, stemming from the combustion process in power plants, emerges as a potential pollution source due to its metal content. Recognized for housing various metals with environmental contamination potential, this study meticulously delves into the metal analysis of chromium (Cr) and lead (Pb) within four distinct samples of fly ash (FA) and bottom ash (BA) sourced from diverse coal-fired power plants across Indonesia. Employing the batch leaching method, the coal ash samples (FABA) underwent a 6-hour immersion in deionized water, replicating environmental scenarios akin to rainwater interaction with coal ash at disposal sites. XRF analysis scrutinized the chemical composition of each sample, while the leaching filtrate underwent analysis via pH meter and AAS to ascertain pH values and the concentrations of Pb and Cr. Results unveiled a substantial pH variation in the leachate, fluctuating from the initial deionized water pH of 7.00 to a range between 6.86 and 9.18. Notably, subsequent leaching indicated undetectable concentrations of Pb in all samples, with most exhibiting low Cr concentrations post-leaching, except for FA-2, FA-4, and BA-4, which displayed modest Cr concentrations. The scarcity or low concentrations of Pb and Cr post-leaching suggest an efficacious process inhibiting heavy metal release. This study offers profound insights into the chemical intricacies of coal ash, underlining its potential environmental ramifications. The absence of detectable heavy metal concentrations post-leaching underscores a minimal risk of environmental pollution, underscoring the imperative to comprehend the chemical reactions intrinsic to the leaching process for optimal waste management strategies.